Na putiakh radikal'noi reformy: perestroika ekonomiki . Na putiakh radikal'noi reformy: perestroika ekonomiki . On the Ways of Radical Reform: Economic Reform . На путях радикальной реформы: перестройка экономики - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Discussion of other countries' taxation policies; the role of science in the development of mechanisms for transition from theory to practice. Featured in the program: Abalkin, Leonid Ivanovich (Economist) Contributors: Voznesenskii, Lev Aleksandrovich (Anchor) Обсуждение опыта других стран в налогообложении и роли науки в разработке механизмов перехода от теории к практике. В программе участвуют: Абалкин, Леонид Иванович (Экономист) Создатели: Вознесенский, Лев Александрович (Ведущий/Ведущая)